Specific Nutritional Intervention And Sensitive Nutrition Through The Whatsapp Group Regarding Knowledge And Attitude Of Posyandu Cadre In Preventing Stunting In Toddlers During The Covid-19 Pandemi In Jembrana District - Ni Rai Sintya Agustini (Sean Institute, 2023)
The Covid-19 pandemic causes an increased risk of stunting prevalence in toddlers. One of the efforts that can be made to prevent stunting is through continuous education. The purpose of this research is to increase the knowledge and attitudes of posyandu cadres regarding specific nutrition and balanced nutrition messages that are given serially through social media in the Jembrana Regency area. The method used in this study is through social media (whatsapp groups) by giving messages in series according to the 4 (four) pillars of balanced nutrition which includes 1) consuming a variety of foods, 2) Clean and Healthy Behavior (PHBS), 3 ) weight monitoring, and 4) physical activity.an increase in the average score of knowledge regarding specific nutrition and balanced nutrition related to the prevention of stunting in toddlers from -36.99 ± -13.0 SD during the pre-test to 17.67 ± 36.32 SDduring the posttest. Posyandu cadres are expected to become agents of change in stunting prevention behavior through education for posyandu cadres to prevent stunting during the Covid-19 pandemic.